Pidana Percobaan Anak Sebagai Pelaku Tindak Pidana Pencurian Dengan Pemberatan - Dian Kartika Putri (Peneliti.net, 2023)
The implementation of diversion in the juvenile justice system as a perpetrator of the crime of theft under aggravating circumstances that the sentence of the Panel of Judges towards diversion in the juvenile justice system as a perpetrator of the crime of theft under aggravating circumstances in Decision Number 8/Pid.Sus-Anak/2018/PN.Btl the defendant was declared as a child offender because at the time of committing the crime the child was under 18 years of age, the defendant had fulfilled the elements of the article charged by the Public Prosecutor. The juvenile defendant had already been convicted in the same case, namely theft with violence, so the Panel of Judges considered that the juvenile must be sentenced according to the Article of criminal law regulations, the juvenile defendant had violated Article 365 paragraph (1) of the Criminal Code. In addition to juridical considerations, the judge also has non-juridical considerations. In this case, the juvenile defendant was not required to seek diversion. The sentence or punishment imposed by the Judge against the Child Defendant is the main punishment, namely Institutional Development in the Special Development Institute for Children for 5 (five) months. Meanwhile, in Decision Number 12/Pid.Sus-Anak/2020/PN Cbn the panel of judges imposed Article 363 paragraph (1) 3rd, 5th of the Criminal Code, Law of the Republic of Indonesia Number 11 of 2012 concerning the Juvenile Criminal Justice System on Criminal Procedure and other relevant laws and regulations. The panel of judges was also correct because it applied the principle of restorative justice in which in its verdict stated that the perpetrator was indeed proven legally and convincingly guilty of committing the crime of